Assistance With Using The E-Commerce Website - Ema Yudiani; Dian Ariani; Ida Aju Brahma Ratih; Tio Devilishanti; Ida Aju Brahmasari (Pusat Riset dan Inovasi Nasional, 2023)
It is difficult for company players to market their products in the current digital era so that the share market expands. As a service partner, Tani Sejahtera Group offers excellent products. Gandus specialty coffee requires online media marketing through the use of e-commerce to promote supportive activities. Use the Rational Unified Process method (RUP) to approach implementation, which is incorrect. Developing web applications is one strategy utilized in problem-solving marketing. A website designed specifically for partners, www.kt Sejahtera Kopi.com, offers online ordering capabilities. Using a website for media promotion will enable you to reach a larger audience, which will benefit farmers in the prosperity group.